Legal Regulation In Tourism Development Without Discrimination - I Made Arya Brata; Cokorde Istri Dian Laksmi Dewi; Karyoto Ahmad (Jurnal Indonesia Sosial Teknologi, 2023)
Tourism plays a vital role in supporting the economy while preserving cultural values. Several things need attention in tourism development, one of which is the emergence and arrangement of tourism destinations, which the development of a sustainable tourism sector must support. Based on this background, the problem was formulated: how to regulate the law against discriminatory acts in the tourism sector and how the phenomenon of discriminatory acts against tourism entrepreneurs in Indonesia. The research method used in this research is normative law research. This study concludes that legal arrangements for safe tourism development are regulated based on Article 26 paragraph (d) of Law no. 10 of 2009 concerning Tourism is obliged to provide comfort, friendliness, protection of security and safety of tourists. In addition, according to Article 23 paragraph (1) letter a of Law no. 10 of 2009, the government and regional governments are obliged to provide tourism information, legal protection, as well as security and safety to tourists